(untitled) (jornal of the libyan geographical society, 2016)
The geographical sphere is a system governed by many laws, and its components are linked by mutual relationships and influences. Climate is one of its components, and any change in the general components of the geographical sphere will necessarily lead to a change in one of its parts. This means that the climate can change or experience fluctuations in its constituent elements. This research paper examines climate fluctuations or changes and their effects on rainfall trends and rates in Libya. Its importance lies in understanding the phenomenon of climate change or fluctuation, its causes, trends, and resulting effects, and in understanding the direction of rainfall change in Libya in order to highlight its indicators. The problem lies in the impact of this change or fluctuation on rainfall rates in Libya, and the resulting environmental effects that harm humans. Several studies have assessed the vulnerability of this harm to the repercussions of climate change. Libya’s location makes it vulnerable to potential impacts on rainfall rates in terms of disruptions to its seasons, timing of its fall, and fluctuations in its quantities, which negatively affects water resources, agricultural production, and pasture fertility. (General Authority for the Environment)